Prevalence and factors associated with scleral hyaline plaque: clinical study of older adults in southeastern Brazil - Horowitz S (Dove Medical Press, 2015)
Soraya Horowitz,1 Nadyr Damasceno,1 Eduardo Damasceno21Department of Ophthalmology, Hospital Naval Marcilio Dias, Rio de Janeiro, 2Department of Ophthalmology, Universidade Federal Fluminense, Niterói, BrazilPurpose: To investigate the prevalence of scleral hyaline plaque among older adults in the city of Niterói in southeastern Brazil. A second goal was to assess the correlation between scleral hyaline plaque and several age-related diseases, including eye diseases and systemic diseases.Methods: The study sample comprised 667 participants who were followed for 15 months. The study had a prospective, longitudinal, observational design that established inclusion and exclusion criteria. The following variables were selected for correlation with scleral hyaline plaque: sex, age, age range, iris color, ethnicity, presence of cataract, moderate to high myopia, age-related macular degeneration (AMD), diabetes mellitus, systemic arterial hypertension, degenerative arthritis, and osteoporosis. These correlations were assessed by means of the χ2 test and Student’s t-test. Multivariate analysis was performed to exclude factors that were potentially associated with aging exclusively but that did not have a direct relationship with hyaline plaque. Binary logistic regression was used to calculate odds ratios, significance, and confidence intervals.Results: Scleral hyaline plaques were found in 177 patients (17.54%). There was a statistically significant association between the presence of hyaline plaques and sex (female), age range (≥70 years old), ethnicity (Caucasian), cataract, moderate to high myopia, systemic arterial hypertension, degenerative arthritis, and osteoporosis (P<0.05). On multivariate binary logistic regression analysis, only female sex, age range (≥70 years), moderate to high myopia, and degenerative arthritis exhibited significant correlation.Conclusion: The prevalence of scleral hyaline plaque in the present study was higher than in previous reports in the medical literature. Several age-related diseases exhibited a correlation with scleral hyaline plaque. The most significant factors associated with scleral hyaline plaque were advanced age, female sex, moderate to high myopia, and degenerative arthritis.Keywords: age-related eye diseases, age-related systemic diseases, factors associated with age-related disorders